Analisis Pemodelan Bangkitan dan Tarikan Pergerakan Transportasi Pada Transportasi pada Tempat Wisata - Daulay, Rizky Ansyori; Hasibuan, Gina Cynthia Raphita; Anas, Ridwan (Syntax Literate, 2025)
This study was conducted to analyze the trip generation and attraction of transportation movements in the Mikey Holiday tourist area of Berastagi, which is one of the main tourist destinations in North Sumatra with a high level of visitation. The increase in tourism activities that is not accompanied by adequate transportation planning has the potential to cause traffic congestion, pollution, and a decline in the quality of traffic services; therefore, an accurate movement prediction model is required as a basis for efficient and sustainable transportation planning. This research employed a quantitative approach using multiple linear regression analysis to identify the factors influencing trip generation and attraction and to develop their mathematical models. Primary data were obtained through field surveys, interviews, and direct observations of vehicle inflows and outflows, visitor characteristics, travel distances and durations, and transportation modes used, while secondary data included the total facility area, parking capacity, and number of employees in the tourist area. The analysis results show that facility area, parking capacity, number of visitors, and number of employees have a positive influence on the level of vehicle movement, whereas travel time has a negative influence. The model intercept values of -40.771 for trip generation and -127.194 for trip attraction indicate the presence of other external factors not included in the model but still affecting movement patterns, such as accessibility conditions and weather factors. Statistical tests demonstrated that all independent variables simultaneously have a significant influence on the dependent variable, with coefficients of determination (R²) of 49% for the trip generation model and 47% for the trip attraction model, indicating that the models are sufficiently representative in explaining variations in vehicle movement at the study location.